The effects of different nutrient strategies on reducing osteochondrosis dissecans lesions and enhancing cartilage properties in pigs - Frantz, N.Z.; Andrews, G.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 80 gilts (PIC 327 × L1050; 86 lb initial BW) were used in an 84-d study to determine the effects of different nutrients on growth performance, carcass composition, the occurrence of osteochondrosis dissecans (OCD) lesions (a cartilage abnormality), and several cartilage criteria. Eight dietary treatments were formulated, consisting of control diet (standard corn-soy diet) or the control diet with fish oil (3.5%) replacing choice white grease; added proline and glycine (300% and 200% of lysine; added leucine, isoleucine, and valine (BCAA; 200%, 100%, and 100% of lysine, respectively); silicon (1000 ppm); copper and manganese (250 ppm and 100 ppm, respectively); added methionine and threonine (150% and 100% of lysine); and a combination of these strategies. The diets were formulated slightly in excess of the pig’s requirement for lysine and to meet minimum true ileal digestibility (TID) ratios for the other essential amino acids. The diets were also formulated to be isocaloric by slightly adjusting the fat (choice white grease) content. Overall, d 0 to 84, pigs fed diets containing BCAA or silicon had greater ADG (P<0.05) than did those fed methionine/threonine or the combination diet; performance of pigs fed the remaining diets was intermediate. Pigs fed methionine/threonine had increased longissimus muscle area (P<0.05), compared with those fed the other dietary treatments, with longissimus muscle area of pigs fed fish oil intermediate. No other carcass responses were affected by dietary treatment (P>0.84). Pigs fed diets containing fish oil or silicon tended (P<0.07) to have an increased number of cartilage abnormalities and a higher score for severity of abnormalities (P<0.05), compared with those of pigs fed the other dietary treatments; scores of pigs fed proline/glycine or copper/manganese were intermediate. Pigs fed fish oil or silicon tended (P<0.07) to have a greater prevalence of potential lesions than did pigs fed the control diet, BCAA, methionine/threonine, or the combination diet; responses to the other dietary treatments were intermediate. Cartilage compression or shear force were unaffected by dietary treatment (P>0.31). In summary, feeding ingredients involved in cartilage and bone metabolism did not improve cartilage properties or reduce the incidence of OCD in gilts relative to the control diet in this study. Feeding diets containing fish oil or silicon caused an increase in the occurrence of potential lesions, the number of cartilage abnormalities, and the scores for severity of abnormalities.
Swine research, 2005 is known as Swine day, 2005
Keywords: Cartilage; Finishing pig; OCD; Swine